Engineering Steam Induced Surface Oxygen Vacancy onto Ni–Fe Bimetallic Nanocomposite for CO2 Electroreduction. Issue 15 (27th February 2022) - He, Qiang; Zhang, Yanxing; Li, Haijing; Yang, Yang; Chen, Shuai; Yan, Wenjun; Dong, Juncai; Zhang, Xian‐Ming; Fan, Xiujun
Abstract: Surface oxygen vacancies (Vo ) regulation is an effective strategy to improve the electrochemical CO2  reduction reaction (CO2 RR) performance by lowering the activation energy barrier of CO2 ; however, the lack of precise control over the local atomic structures severely hinders the large‐scale application of Vo ‐activated electrocatalyst for CO2 RR. Herein, an efficient strategy to facilitate CO2  activation is developed by introducing Vo into transition metal nanoparticles (NPs) with a steam‐assisted chemical vapor deposition method. With the steam process, abundant surface Vo are introduced into the assembled Ni–Fe bimetallic NPs composite (H‐NiFe/NG), which adjust surface Ni/Fe atoms to low‐valent coordinatively unsaturated Ni (+1)/Fe (+2) sites, serving as electron‐rich centers to adsorb and activate inert CO2  molecules. The as‐prepared H‐NiFe/NG composite exhibits excellent catalytic performance with a maximum Faradaic efficiency of 94% at −0.80 V (vs RHE) for CO production with remarkable stability. The density function theory calculations corroborate that the Ni atoms around surface Vo significantly lower the energy barrier for COOH* intermediate formation, which gives a low overpotential for reducing CO2  to CO, exhibiting superior CO2 RR performance. This general synthetic strategy provides a new insight to introduce surface Vo on transition metal for efficient CO2  reduction. Abstract : A steam‐assisted chemical vapor deposition method is reported to facilitate the CO2  reduction reaction on iron‐group metal. With the steam process, abundant surface oxygen vacancies are introduced into the assembled Ni–Fe bimetallic nanoparticle composites, which effectively activate the basal plane metal active sites, serving as electron‐rich centers to adsorb and activate inert CO2  molecules.